2024
DOI: 10.4102/hts.v80i1.9049
|View full text |Cite
|
Sign up to set email alerts
|

Implicit religion, Anglican cathedrals, and spiritual wellbeing: The impact of carol services

Leslie J. Francis,
Ursula McKenna,
Francis Stewart

Abstract: Rooted in the field of cathedral studies, this paper draws into dialogue three bodies of knowledge: Edward Bailey’s notion of implicit religion that, among other things, highlights the continuing traction of the Christian tradition and Christian practice within secular societies; David Walker’s notion of the multiple ways through which in secular societies people may relate to the Christian tradition as embodied within the Anglican Church and John Fisher’s notion of spiritual wellbeing as conceptualised in rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…A third strand of research has been concerned with mapping the characteristics of people who attend cathedral carol services. This strand includes qualitative studies reported by Phillips (2010), Murphy (2016), andPike (2022), and quantitative studies reported by Walker (2012aWalker ( , 2012bWalker ( , 2013aWalker ( , 2013bWalker ( , 2015 Francis, McKenna and Stewart (2024) isolated the responses of 404 participants who self-identified as not believing in God and who had completed the psychological type scales and who had completed the Fisher spiritual wellbeing measure just before the close of the service. They reported that among participants who did not believe in God, people who felt connected with Liverpool Cathedral and who felt connected with the carol service in such a way that they return year-on-year derived more spiritual benefit from their attendance than those who appeared to be more casual attenders.…”
Section: Research Aimmentioning
confidence: 99%
“…A third strand of research has been concerned with mapping the characteristics of people who attend cathedral carol services. This strand includes qualitative studies reported by Phillips (2010), Murphy (2016), andPike (2022), and quantitative studies reported by Walker (2012aWalker ( , 2012bWalker ( , 2013aWalker ( , 2013bWalker ( , 2015 Francis, McKenna and Stewart (2024) isolated the responses of 404 participants who self-identified as not believing in God and who had completed the psychological type scales and who had completed the Fisher spiritual wellbeing measure just before the close of the service. They reported that among participants who did not believe in God, people who felt connected with Liverpool Cathedral and who felt connected with the carol service in such a way that they return year-on-year derived more spiritual benefit from their attendance than those who appeared to be more casual attenders.…”
Section: Research Aimmentioning
confidence: 99%